1995
DOI: 10.1164/ajrccm.152.6.8520742
|View full text |Cite
|
Sign up to set email alerts
|

Identification of patients with acute lung injury. Predictors of mortality.

Abstract: A recent North-American-European Consensus Conference proposed new, uniform criteria for the definition of acute lung injury, in part to facilitate earlier identification of patients for clinical trials. However, these criteria have not been evaluated prospectively. We designed a prospective cohort study of 123 consecutive patients with acute lung injury prospectively identified on admission to the adult intensive care units of a tertiary care university hospital. The objectives were to determine if selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
268
8
14

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 455 publications
(315 citation statements)
references
References 22 publications
25
268
8
14
Order By: Relevance
“…Initial use of combination therapy reduces the likelihood of inappropriate therapy, and has been recommended to avoid the emergence of antimicrobial resistance and to enhance the killing produced by antimicrobials acting synergistically, particularly against VAP produced by P. aeruginosa. 2 However, Garnacho-Montero et al 21 demonstrated that monotherapy with only one active antibiotic provided similar outcomes compared with combination therapy with two active antimicrobials, and suggested that switching to monotherapy once the susceptibility is documented was feasible and safe even against P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Initial use of combination therapy reduces the likelihood of inappropriate therapy, and has been recommended to avoid the emergence of antimicrobial resistance and to enhance the killing produced by antimicrobials acting synergistically, particularly against VAP produced by P. aeruginosa. 2 However, Garnacho-Montero et al 21 demonstrated that monotherapy with only one active antibiotic provided similar outcomes compared with combination therapy with two active antimicrobials, and suggested that switching to monotherapy once the susceptibility is documented was feasible and safe even against P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of acute lung injury included evaluation of the chest radiograph and arterial oxygenation using the PaO 2 /FiO 2 coefficient (partial pressure of arterial oxygen to the fraction of inspired oxygen). 2 We defined the presence of the acute respiratory distress syndrome as the presence of a generalized pulmonary infiltrate and a lung injury score 42.5, 14 and the presence of shock as systolic arterial pressure of o90 mm Hg with signs of peripheral hypoperfusion or need for continuous infusion of vasopressor or inotropic agents.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most frequently studied indices is the Pa,O 2 / FI,O 2 , although contradictory results concerning its ability to predict outcome have been reported in adult AHRF/ARDS [2,[27][28][29][30][31][32][33][34][35]. Some authors have argued that the ratio may not be predictive at inclusion, but after 24 or 48 h [30,31].…”
Section: Discussionmentioning
confidence: 99%